2014
DOI: 10.1093/hmg/ddu118
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric muscle challenge shows osteopontin polymorphism modulation of muscle damage

Abstract: A promoter polymorphism of the osteopontin (OPN) gene (rs28357094) has been associated with multiple inflammatory states, severity of Duchenne muscular dystrophy (DMD) and muscle size in healthy young adults. We sought to define the mechanism of action of the polymorphism, using allele-specific in vitro reporter assays in muscle cells, and a genotype-stratified intervention in healthy controls. In vitro reporter constructs showed the G allele to respond to estrogen treatment, whereas the T allele showed no tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…This finding supports a role of SPP1 rs28357094 as a modulator of GC response in DMD, rather than of disease progression itself. This is in concordance with several preclinical studies of SPP1 promoter function; the minor G allele at rs28357094 decreases transcriptional activity of the gene at baseline,6 but shows a 3-fold increase in gene expression in response to steroids, whereas the common allele leaves expression unchanged by steroids 7. Consistent with a steroid-induced alteration of SPP1 expression, differences in SPP1 mRNA levels between genotypes were not found in vivo in DMD diagnostic muscle biopsies obtained prior to GC treatment 27.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding supports a role of SPP1 rs28357094 as a modulator of GC response in DMD, rather than of disease progression itself. This is in concordance with several preclinical studies of SPP1 promoter function; the minor G allele at rs28357094 decreases transcriptional activity of the gene at baseline,6 but shows a 3-fold increase in gene expression in response to steroids, whereas the common allele leaves expression unchanged by steroids 7. Consistent with a steroid-induced alteration of SPP1 expression, differences in SPP1 mRNA levels between genotypes were not found in vivo in DMD diagnostic muscle biopsies obtained prior to GC treatment 27.…”
Section: Discussionsupporting
confidence: 91%
“…5 The rs28357094 polymorphism alters transcription at baseline 6 and in response to steroid hormones. 7 The LTBP4 locus was identified by genome-wide mapping in a murine model of muscular dystrophy. 8 Subsequently, a LTBP4 haplotype was associated with variable LoA in 254 patients with severe dystrophinopathy (United Dystrophinopathy Project).…”
mentioning
confidence: 99%
“…A genetic study showed that gene polymorphisms in OPN modulate the response of adult volunteer muscle to inflammation detected by magnetic resonance imaging after damaging contractions (Barfield et al . 2014), followed by another study showing that these same polymorphisms alter the clinical severity of DMD (Bello et al . 2015).…”
Section: Discussionmentioning
confidence: 97%
“…2013) and increased damage in response to eccentric contraction in young adults (Barfield et al . 2014). In normal skeletal muscle in homeostatic conditions, OPN expression is very low or undetectable.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, steroid hormones may play a role in SPP1 regulation. The rs28357094T haplotype reduces the responsiveness of SPP1 promoter to estrogen-driven transcriptional activation [36]. Moreover, a study performed in malignant astrocytoma cell lines demonstrated binding of the proximal promoter element (surrounding the rs28357094 site) by the glucocorticoid receptor [37].…”
Section: Osteopontin: a Multi-faceted Modifiermentioning
confidence: 99%